Preclinical Characterization of a Novel Anti-Cancer PD-L1 Inhibitor RPH-120 - Kulikov, Andrey; Shipaeva, Elena; Dmitrieva, Anastasia; Batrak, Vera; Shipunov, Georgy; Guy, Colin; Smith, Jill; Zhang, Ran; Zhang, Michael; Duan, Jeff; Chestukhin, Anton; Barbashov, Sergei; et al. (Frontiers in Pharmacology, 2021)
RPH-120 is a novel fully human anti-PD-L1 IgG1 monoclonal antibody with specifically designed Asn300Ala mutation in Fc fragment. Surface plasmon resonance assay showed that affinity of the RPH-120 to the dimeric form of human PD-L1-Fc fusion protein was much higher than affinity to the monomeric His-tagged PD-L1. Further binding studies demonstrated that RPH-120 is able to bind to human and monkey but not mouse PD-L1. Tissue cross-reactivity study showed good comparability of human and Cynomolgus monkeys tissue staining. Bioactivity was assessed using mixed lymphocyte reaction assay. This study revealed that RPH-120 was able to activate T cells preventing PD1/PD-L1 interaction. Antitumor efficacy was analyzed in HCC-827 lung cancer xenografts in humanized CD34+ mice at three dosage levels: 20 mg/kg, 80 mg/kg, and 200 mg/kg. RPH-120 demonstrated significant tumor growth inhibition, and this inhibition was comparable to that of atezolizumab. In a single dose toxicity, toxicokinetic and dose range finding study performed in Cynomolgus monkeys, RPH-120 was administered via intravenous (IV) bolus or 60-minute IV infusion, followed by 8-week recovery period. An acceptable toxicokinetic profile was demonstrated and administration at doses of up to 200 mg/kg was well tolerated by all animals. In conclusion, RPH-120 revealed promising in vitro and in vivo activity and safety. RPH-120 is a potent anti-PD-L1 drug candidate for cancer immunotherapy.